2009
DOI: 10.1371/journal.ppat.1000643
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria Exploit Host Hyaluronan for Efficient Extracellular Replication

Abstract: In spite of the importance of hyaluronan in host protection against infectious organisms in the alveolar spaces, its role in mycobacterial infection is unknown. In a previous study, we found that mycobacteria interact with hyaluronan on lung epithelial cells. Here, we have analyzed the role of hyaluronan after mycobacterial infection was established and found that pathogenic mycobacteria can grow by utilizing hyaluronan as a carbon source. Both mouse and human possess 3 kinds of hyaluronan synthases (HAS), des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…HAS1 has a c-Maf binding site in its promoter region, c-Maf siRNA inhibits HAS1 expression, and HAS1 siRNA reduces growth of M. tuberculosis H37Rv in CD14 hi monocytes, suggesting that c-Maf regulates intracellular growth of M. tuberculosis in part through HAS1. The latter is an enzyme that controls production of hyaluronan, an abundant component of the extracellular matrix that can be broken down by mycobacterial hyaluronidases and used as a carbon source to enhance extracellular replication of M. tuberculosis (15). Hyaluronan is also present in the cytoplasm (34), and we found that HAS1 expression was markedly upregulated in M. tuberculosis H37Rv-infected CD14 hi cells but not in CD14 lo CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…HAS1 has a c-Maf binding site in its promoter region, c-Maf siRNA inhibits HAS1 expression, and HAS1 siRNA reduces growth of M. tuberculosis H37Rv in CD14 hi monocytes, suggesting that c-Maf regulates intracellular growth of M. tuberculosis in part through HAS1. The latter is an enzyme that controls production of hyaluronan, an abundant component of the extracellular matrix that can be broken down by mycobacterial hyaluronidases and used as a carbon source to enhance extracellular replication of M. tuberculosis (15). Hyaluronan is also present in the cytoplasm (34), and we found that HAS1 expression was markedly upregulated in M. tuberculosis H37Rv-infected CD14 hi cells but not in CD14 lo CD16 + monocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Of these genes, 22 have c-Maf binding site in their promoter region. Among these genes, we selected that encoding HAS1, which was shown to enhance extracellular growth of M. tuberculosis H37Rv in the lungs (15). We also selected ZIP5 and TTC22, which are highly expressed in CD14 hi monocytes after stimulation with M. tuberculosis H37Rv.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). As mentioned before, secreted bacterial hyaluronan lyases have been shown to act as spreading factors to enhance invasion through degrading the host extracellular matrix as well as act as metabolic enzymes capable of generating sugars from host HA to promote bacterial growth during deep tissue infections (14). Alternatively, one recent study of the biofilm composition of two mucoid S. maltophilia strains isolated from cystic fibrosis patients identified a unique structure comprised of D-lactate-substituted, O-acetylated GalA and GlcA blocks (68).…”
mentioning
confidence: 97%
“…In particular, HA lyases secreted by Group A Streptococcus are thought to act as spreading factors, enabling bacteria and toxins to disseminate throughout the host by degrading the high molecular weight HA present in the extracellular matrix (13). In Mycobacterium tuberculosis, secreted HA lyases generate low molecular weight sugars from HA that serve as carbon source for bacteria to replicate in deep tissue infections (14). In the case of P. aeruginosa biofilm formation, the periplasmic alginate lyase AlgL regulates the chain length and concentration of alginate in the periplasm during secretion (15).…”
mentioning
confidence: 99%